Short-term voiding patterns after vaginal hysterectomy and pelvic floor repair - Lim, Poh T.; Lee, Jill C. S.; Han, How C. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Post-operative transient voiding dysfunction is a known complication of vaginal hysterectomy (VH) with pelvic floor repair (PFR). This study aims to determine the duration of urinary catheterization prior to resumption of normal voiding and hospital length of stay for patients who have undergone VH, PFR with or without concomitant application of transvaginal mesh (TVM) and/or mid-urethral sling (MUS). Methods: This is a retrospective cohort study of women who underwent VH with PFR at a single urogynaecology centre in Singapore between 01 October 2016 and 30 September 2017. Patients’ files were reviewed for data collection and analysis. Results: A total of 238 women with VH with PFR were studied, of whom 68 (28.6%) did not have any implant, 60 (25.2%) had only TVM, 50 (21.0%) had only MUS, and 60 (25.2%) had both TVM and MUS. Overall, 1/68 (1.5%) patients without implants, 16/110 (14.5%) patients with one implant and 13/60 (21.7%) patients with two implants failed at least 1 inpatient voiding trial. Patients undergoing VH PFR without implants had shorter duration of catheterization compared to those with concomitant implants (2.2 versus 5.6 days, p<0.01). Duration of catheterization was shorter in patients with only MUS compared to patients with only TVM (3.5 versus 4.7 days, p<0.01). Patients with single implant had significantly shorter duration of catheterization compared to those with two implants (4.2 versus 5.6 days, p=0.001). Conclusions: One in 68 patients with VH with PFR without implants experienced short term voiding difficulties. This risk increased to 1 in 5 when concomitant implants were inserted.